2014
DOI: 10.1088/0004-637x/791/2/84
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field Restructuring Associated With Two Successive Solar Eruptions

Abstract: We examine two successive flare eruptions (X5.4 and X1.3) on 2012 March 7 in the NOAA active region 11429 and investigate the magnetic field reconfiguration associated with the two eruptions. Using an advanced non-linear force-free field (NLFFF) extrapolation method based on the SDO/HMI vector magnetograms, we obtain a stepwise decrease in the magnetic free energy during the eruptions, which is roughly 20%−30% of the energy of the pre-flare phase. We also calculate the magnetic helicity, and suggest that the c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 27 publications
(37 reference statements)
3
24
0
3
Order By: Relevance
“…In 2015 June AR 12371 exhibited elevated activity, somewhat similar to AR 11429 in 2012 March (Liu et al 2013(Liu et al , 2014cWang et al 2014;Sun et al 2015). The active region produced a CME of about 1200 km s −1 associated with an M3.0 flare from N13 • E45 • that peaked at 17:36 UT on June 18, a CME of about 1300 km s −1 associated with an M2.0 flare from N12 • E13 • peaking at 01:42 UT on June 21, a CME of about 1000 km s −1 associated with an M6.5 flare from N13 • W05 • peaking at 18:23 UT on June 22, and another one of about 1700 km s −1 associated with an M7.9 flare from N10 • W42 • peaking at 08:16 UT on June 25.…”
Section: The 2015 June Eventmentioning
confidence: 81%
“…In 2015 June AR 12371 exhibited elevated activity, somewhat similar to AR 11429 in 2012 March (Liu et al 2013(Liu et al , 2014cWang et al 2014;Sun et al 2015). The active region produced a CME of about 1200 km s −1 associated with an M3.0 flare from N13 • E45 • that peaked at 17:36 UT on June 18, a CME of about 1300 km s −1 associated with an M2.0 flare from N12 • E13 • peaking at 01:42 UT on June 21, a CME of about 1000 km s −1 associated with an M6.5 flare from N13 • W05 • peaking at 18:23 UT on June 22, and another one of about 1700 km s −1 associated with an M7.9 flare from N10 • W42 • peaking at 08:16 UT on June 25.…”
Section: The 2015 June Eventmentioning
confidence: 81%
“…Two of the main sources of successive CMEs are homologous and sympathetic eruptions. Solar observations have revealed that recurrent CMEs occur from the same active region, often associated with homologous flares (Schmieder et al 1984;Moon et al 2003;Liu et al 2014a,b;Wang et al 2014a). Sympathetic CMEs, when the eruption of one CME triggers another, is another source of successive CMEs in relatively close angular and temporal separation (see Fig.…”
Section: Plasma Evolutionmentioning
confidence: 98%
“…They include several major flares from well-studied ARs. Among others, NOAA AR 11158 produced the first Xclass (X2.2) flare in Solar Cycle 24 (e.g., Schrijver et al 2011), 11429 produced the largest (X5.4) flare so far in this cycle (e.g., Wang et al 2014), 12017 produced the "best-observed" X1.0-class flare (e.g., Kleint et al 2015), and 12192, the largest sunspot group so far in the cycle, produced many (6 X-and 24 M-class) but CMEpoor events (e.g., Sun et al 2015: 4 X-and 2 M-class events are listed in Table 1). Almost all the events in this table occurred at PILs within the AR's magnetic structure itself.…”
Section: Properties Of Ars and Flare Eventsmentioning
confidence: 99%